MODEL INOVASI PELAYANAN PUBLIK BERBASIS KOLABORASI PENTAHELIX DALAM MENINGKATKAN DAYA SAING DAERAH - Samson Laurens (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
This research examines the development of public service innovation models based on pentahelix collaboration in enhancing regional competitiveness through a systematic literature review approach. The analysis was conducted on 127 peer-reviewed articles published between 2018- 2024, using the PRISMA framework and SPIDER analysis model. The results show that pentahelix collaboration implementation has a significant impact on improving public service quality, with an implementation success rate of 78%. Critical factors influencing implementation success include leadership support (92%), shared vision (85%), and communication effectiveness (88%). Model implementation resulted in service time reduction by 45%, operational cost reduction by 32%, and public satisfaction index increase by 28%. The developed implementation framework encompasses four main dimensions: structural, process, technology, and social, with a phased approach including initiation, development, and implementation. Major implementation challenges were identified in aspects of overlapping authority, digital infrastructure gaps, and resistance to change. The research provides strategic recommendations for each pentahelix stakeholder to optimize their roles and contributions in enhancing regional competitiveness through public service innovation.